On the margins: Jews and Muslims in interwar Berlin - Jonker, Gerdien (Muslim minorities, 2020)
Crossroads --The Spaces in Between -- The Hiking Club: S.M. Abdullah and the Oettinger Women -- An Artist's View: Lisa Oettinger Between 'Civilizations' -- The Sting of Desire: Hugo Marcus's Theology of Male Friendship -- The Rebels: Luba Derczanska and Her Friends -- An Indian Muslim in Jewish Berlin: Khwaja Abdul Hamied.